Student's Knowledge of Adherence to Handwashing with Soap and Running Water during Adaptation of New Habits - Nuurkhalisa Rachmasari; Wuri Utami; Umi Laelatul Qomar (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Countries in the world are currently facing a COVID-19 pandemic. World Health Organization recommended one of COVID-19 prevention by washing hands with soap and running water. Indonesia's government set a new adaptation by allowing schools to conduct face-to-face learning in the green or yellow zone. Each school has to provide and practice handwashing using soap before students start the learning process. To determine the student's knowledge of adherence to handwashing with soap and running water in MTs Cokroaminoto Dawuhan, Madukara District of Banjarnegara Regency. This study was a descriptive quantitative design with a cross-sectional approach. The population in this study was all students of MTs Cokroaminoto Dawuhan, Madukara. Data collection used questionnaires and analyzed using univariate analysis through SPSS. One hundred thirtynine respondents were in good knowledge (84.2%), twenty-four respondents were in enough level (14.5%), and only two respondents were in poor levels (1.2%). Sequentially for adherence and non-adherence levels, 113 respondents (68.5%) and six respondents (31.5%). The adherence levels of students to handwashing in the adaptation of new habits of the COVID-19 pandemic have good knowledge and adherence in handwashing with running water. Further study can examine the factors influencing students' adherence to handwashing with running water during the COVID-19 pandemic.